THE EFFECT OF PROJECT-BASED LEARNING ON CREATIVE THINKING SKILLS TOWARD PRESERVICE TEACHER IN PRIMARY TEACHER EDUCATION PROGRAM - Fatimah, Siti (JPI (Jurnal Pendidikan Indonesia), 2018)
This study aims to determine the effect of project-based learning on creative thinking skills toward preservice teachers in primary teacher education programs in electricity material and the great improvement of creative thinking skills. This research was a Quasi-Experiment toward students in the fourth semester amounted to 2 classes. The data collection was done in the form of observations and creative thinking skills test. Analysis of the data using the Mann Whitney U Test. The results showed: 1) Project-based learning has significant effects on the creative thinking skills of students; 2) Improvement of students' creative thinking skills using free project-based learning is better than guided project-based learning.